Integrating Community Driven-approach and CSR-supported Coastal Defense: Waste-tire Wave Breakers (APO) in Tanjung Pakis West Java - Mochammad Rizqy Maulana; Dhavani Ardyas Putera; Muhammad Bima Oktageannar (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2026)
Coastal erosion along the northern coast of Java poses significant environmental and socio-economic challenges, particularly due to mangrove conversion into aquaculture. In Tanjung Pakis, West Java, the community group of Elang Laut, in collaboration with CarbonEthics and Planet Ban, implemented waste-tire wave breakers (Alat Pemecah Ombak, APO) as a community-driven coastal protection strategy supported by a CSR-based circular economy model. This study evaluates APO effectiveness by integrating multi-temporal shoreline analysis using Sentinel-2 imagery and the Digital Shoreline Analysis System (DSAS) for 2018–2024, combined with socio-economic surveys and focus group discussions. The analysis shows that post-installation (2022–2024), mean shoreline erosion decreased by 4.73 m/yr, while accretion increased by 2.85 m/yr, reducing overall shoreline retreat from −9.79 m/yr to −5.41 m/yr. Impacts were concentrated in APO-installed areas, indicating effective wave attenuation and sediment trapping. Socio-economic impacts findings reveal an average 11.1% increase in household income, driven by improved fishpond protection and productivity. CSR support enabled construction, maintenance, and local labor involvement, strengthening community ownership. The study demonstrates that APOs are most effective as complementary measures to ecosystem-based restoration. Combined with community participation and CSR support, APOs offer a viable hybrid approach to enhancing coastal resilience in vulnerable tropical environments.